The Usage of Information System for Documenting Number of Users of Research Laboratory at Faculty of Pharmacy, Universitas Muhammadiyah Surakarta: Pemanfaatan Sistem Informasi dalam Dokumentasi Jumlah Pengguna Laboratorium Penelitian di Fakultas Farmasi Universitas Muhammadiyah Surakarta - Hidayatullah, Muhammad Haqqi; Santoso, Broto; Wathony, Al; Riyanto, R (Prosiding University Research Colloquium, 2023)
Laboratories are important infrastructure for learning and research in academic sector, especially in the field of science, such as the Faculty of Pharmacy, Muhammadiyah University of Surakarta. In fact, laboratory utility records are obtained manually by writing them in a laboratory activity logbook. The time required was not efficient and did not visualize real time data are obstacles to create a recapitulation of users data per time. The system has been built by utilizing the features in Google Forms and Google Sheets. Laboratory users has been asked to fill in the required data for the main database. Furthermore, users are instructed to make a presence using Google Forms when entering and leaving the laboratory. The data can be processed and analyzed according to laboratory needs. There were 50 data users who have registered to use the research laboratory. The result is that the system has been running properly for documenting laboratory user occupancy. The system can still be upgraded if necessary. The limitations of this system are the system still needs to be improved continuously, there is no system management level, and data processing automation needs to be adjusted manually at the beginning.